Factors affecting farmers’ willingness and ability to adopt and retain vitamin A-rich varieties of orange-fleshed sweet potato in Mozambique - Jenkins, M.; Shanks, C.B.; Brouwer, R.; Houghtaling, B. (Springer, 2018)
The addition of orange-fleshed sweet potato (OFSP) to the food environment is an effective nutrition-sensitive agricultural approach to improve vitamin A intakes. However, the adoption of this biofortified crop merits further study. The objective of our research was to understand factors that affect Mozambican farmers’ adoption and retention of OFSP varieties, with a specific interest in the retention of planting material. Field research was conducted in three provinces of Mozambique during 2015. Provinces with different OFSP intervention histories were selected to allow for the identification of site-specific factors and the impact of variable approaches over time. Qualitative inquiry was used to assess participants’ progress through the five stages of the Innovation-Decision process in the Diffusion of Innovations Theory. Ninety-five producers, consumers, and market stakeholders of OFSP participated in semi-structured in-depth interviews and focus groups. Results indicate that diverse factors influenced the adoption and retention of OFSP, including organoleptic qualities, taste preferences, access to planting material, agronomic traits, environmental conditions, lack of capital for inputs and labor, unstable markets, and limited sharing of information and planting material across farmer networks. Current OFSP varieties were acceptable to Mozambican farmers and consumers, but there are several remaining challenges to reaching a critical mass such as lack of access to planting material, perceptions of superior drought tolerance of white-fleshed sweet potato (WFSP), and the belief that OFSP requires additional effort to cultivate (e.g. weed removal, measuring space between plants). Key recommendations which may be considered in future planning for OFSP interventions in Mozambique and other countries include enabling decentralized vine multipliers to provide vines to community members at no cost, continued focus on breeding and distribution of more drought tolerant varieties of OFSP, and training on the similarities in agronomic practices required for producing and preserving OFSP and WFSP.